THE INFLUENCE OF ORGANIZATIONAL CULTURE AND TRAINING ON EMPLOYEE PERFORMANCEAT BUKIT ASAM, TBK - Marthien Pratama; Badia Perizade; Marlina Widiyanti; Zunaidah Zunaidah (President University, 2021)
This research was conducted to determine and analyze how the influence of organizational culture and training on employee performance at PT. Bukit Asam, Tbk. The population in this study were all permanent employees at PT. Bukit Asam, Tbk in 2018 as many as 2,122 employees. The sampling technique used in this study was Proportionate Stratified Random Sampling. The sample used in this study were 100 permanent employees of PT. Bukit Asam, Tbk in 2018. The data collection method used a questionnaire and analyzed using multiple linear regression analysis. The results showed that organizational culture has a positive and significant effect on the performance of employees of PT. Bukit Asam, Tbk. Training has a positive and significant effect on the performance of the employees of PT. Bukit Asam, Tbk. Organizational culture needs to improve relations between employees in collaborating with other work members to provide the best results for the company. The training material provided needs to be adapted to the work field of employees undergoing training with effective and efficient methods.Keywords: Organizational Culture, Training, Employee Performance